Penalidades administrativas expulsivas e a governança pública conforme o Índice Integrado de Governança e gestão (IGG) e o índice ESG - Environmental, Social and Governance - do setor público (IESGO) - Oliveira, Jean Carlos de (2025)
The objective was to diagnose the most frequent penalties and irregularities and the number of cases involving acts of administrative impropriety and to assess whether there is a correlation with the increase in public governance programs. In addition, to demonstrate disciplinary administrative processes as public policies for the promotion and development of public governance. Based on an eminently qualitative approach, the research verified the incidence of cases of administrative convictions for administrative impropriety and other most frequent irregularities applied to public servants, in accordance with Law 8.112/90, of fifteen of the federal agencies and entities with direct activity in Paraná, with records on the Transparency Portal of the Comptroller General of the Union, as well as whether there is a correlation between the level of expulsive penalties and compliance, or not, with the fundamental principles of public governance provided for in Decree No. 9.203/2017 and measured by the Integrated Governance and Management Index (iGG) and the ESG Index - Environmental, Social and Governance - of the Public Sector (iESGo).